Organizational behavior : experiences and cases - Marcic, Dorothy; Seltzer, Joseph; Vaill, Peter (Cincinnati, Ohio : South-Western College, 2001)
Introduction to organizational behavior. Personality and attitudes. Perception and attribution. Learning and reinforcement. Work motivation. Motivating performance: goal setting and reward systems. Work stress. Group and team behavior...
Keywords: Organization; Organizational behavior -- Problems, exercises, etc